After hours - Aicher, Lynda (The Boardroom series, 2018)
The Boardroom. After hours, it's where Bay area moguls indulge their fantasies. Ties are lossened, inhibitions, too. Assistant Avery Fast watched from a distance mouth gaping, blood roaring wildly in her ears as she stared at the naked woman on the table before her. At executive Carson Haggert ordering a man to pleasure her. It made her feel guilty, embarrassed... and hot. Carson watched and waited. Waited for Avery to notice him in the Boardroom. Waited for her to like what she saw. Waited to see what she'd do the next day. And the next. He couldn't let her go -- not when she'd seen what goes on in the Boardroom. He couldn't stop thinking about the desire in her eyes, the flush o her cheeks, her obvious arousal. Getting her to join was easy. But now Carson wants Avery all to himself.